Knowledge, Attitudes and Professional Behavior of Silver Diamine Fluoride among Dental Personnel: A Systematic Review - Intan Elliayana Mohammed; Nursharhani Shariff; Muhammad Faiz Mohd Hanim; Mohd Yusmiaidil Putera Mohd Yusof; Budi Aslinie Md Sabri; Nor Faezah Md Bohari; Annapurny Venkiteswaran (MDPI AG, 2022)
Apart from the major drawback of black staining once lesion is arrested, few studies have indicated that dental personnel's perception and attitude towards silver diamine fluoride (SDF) influences its usage. This report aims to provide a systematic review presenting dental personnel's knowledge, attitudes, and perceptions, (KAPs) regarding SDF. A search of multiple electronic literature databases and a manual search were performed. The review was reported according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses 2020 statement. A comprehensive search yielded 719 publications and 14 cross-sectional studies matching the inclusion criteria. Awareness of SDF among respondents ranged from 29.6% to 87.8%, whereas awareness of its use in dentistry ranged from 14.4% to 94.5%. Regarding attitude towards SDF, the mean score ranged from 3.39 to 14.35. An increase in knowledge of and attitude towards SDF is significantly associated with the usage of SDF and may increase the usage of SDF. This review provides vital information on dental personnel's KAPs regarding SDF. It is anticipated that the adaptation of SDF usage will be more widespread in the future, especially among children. Findings from the review may assist intervention programs to change misperceptions and to enhance awareness regarding SDF among dental personnel.